Centering of Data in Principal Component Analysis in Ecological Ordination - Basnet, Khadka (Tribhuvan University Journal, 2010)
Available with full-text. Key words: Data; Ecological Ordination Tribhuvan University Journal Volume XVI, 1993 Page: 29-34 Uploaded date: 3 October, 2010